ANALISIS PUTUSAN KEPAILITAN MAHKAMAH AGUNG NOMOR 769 K/PDT.SUS-PAILIT/2016 MENGENAI PEMBERESAN HARTA PAILIT (BOEDEL PAILIT) - Selly Virginia; F. X. Suyud Margono (Fakultas Hukum Universitas Tarumanagara, 2019)
The progress of the economy in Indonesia is currently experiencing very rapid development, giving rise to very tight competition between business actors. In the business world the need for funds is a basic necessity that must be met by businesses to maintain and support the continuity of their business activities, so that to overcome the problem of capital needs, loan capital in the form of accounts payable is a solution that is often taken by businesses. Of course business people need funds or capital to strengthen their position in the economic sphere and intense competition in this era of globalization. Funds or capital needed by business people to run their businesses are obtained from debt facilities (loans or loans) obtained through individuals or financial institutions, which are used to increase their business capital both in the form of short-term, medium-term and long-term debt. This paper identifies one problem, namely whether someone / person is not declared bankrupt can be made bankrupt? (Case Study of Decision of the Supreme Court Number 769 K / Pdt.Sus-Pailit / 2016). The method used in this study is a type of analytical descriptive legal research and uses primary and secondary legal materials. The results of the study show that the property of a person or person referred to herein is the property of the Director (along with 2 partners) who at the beginning had made an agreement in order to make the asset in the name of The Hwie Gwan a guarantee by both parties.